2017
DOI: 10.4028/www.scientific.net/msf.891.533
|View full text |Cite
|
Sign up to set email alerts
|

Ni-NiO Porous Preform with Controlled Porosity Using Al<sub>2</sub>O<sub>3</sub> Powder

Abstract: The Ni-NiO skeleton seems to be a good candidate for various applications in industry such as corrosion-proof filters or components in refrigerating systems and as preforms for reactive infiltration with molten metals.The present work was focused on preparation of Ni-NiO composite with higher, controlled porosity. Sintering of pure Ni powder always leads to a substantial closed porosity in almost whole sample volume [1,2]. To eliminate this, we added Al2O3 particles with diameter of-32 +20 μm into the Ni powde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 7 publications
2
4
1
Order By: Relevance
“…It has been evidenced in our previous work [34], and in agreement with others [35,36], that the weight gain was caused solely by the formation of NiO layers on the surface of Ni particles as a result of thermal oxidation. Moreover, it has been reported that the NiO growth gave rise to the sample open porosity [34].…”
Section: Impact Of the Sample Weight And Dimensionssupporting
confidence: 92%
See 4 more Smart Citations
“…It has been evidenced in our previous work [34], and in agreement with others [35,36], that the weight gain was caused solely by the formation of NiO layers on the surface of Ni particles as a result of thermal oxidation. Moreover, it has been reported that the NiO growth gave rise to the sample open porosity [34].…”
Section: Impact Of the Sample Weight And Dimensionssupporting
confidence: 92%
“…It has been evidenced in our previous work [34], and in agreement with others [35,36], that the weight gain was caused solely by the formation of NiO layers on the surface of Ni particles as a result of thermal oxidation. Moreover, it has been reported that the NiO growth gave rise to the sample open porosity [34]. In an attempt to understand the role of Al 2 O 3 particle size in pore formation and distribution, the weight gain was associated with the sample porosity determined by the Archimedes' principal-based method.…”
Section: Impact Of the Sample Weight And Dimensionssupporting
confidence: 92%
See 3 more Smart Citations